1979
DOI: 10.3171/jns.1979.50.4.0499
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen-receptor protein in intracranial meningiomas

Abstract: The increased frequency of meningiomas in women compared with men, and the rapidly progressive course of these tumors in pregnant patients suggest that hormones may be involved in this disease. Tumor tissue from six patients with meningiomas was analyzed for estrogen-receptor protein. Two patients had tumors with very high concentrations of this protein, approaching that found in hormonally sensitive breast carcinoma. The biochemical and possible clinical significance of these findings is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
57
1
3

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(66 citation statements)
references
References 20 publications
5
57
1
3
Order By: Relevance
“…In our study of 116 meningiomas, none of them display ER immunoreactivity. On the other hand, we find that the majority of meningiomas is immunoreactive for PR, in agreement with other authors [5][6][7][8]16,17 . The presence of PR and lack of ER has led to believe that these PRs are estrogen independent, unlike PRs present in other hormoneregulated tumors, such as breast and uterus.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study of 116 meningiomas, none of them display ER immunoreactivity. On the other hand, we find that the majority of meningiomas is immunoreactive for PR, in agreement with other authors [5][6][7][8]16,17 . The presence of PR and lack of ER has led to believe that these PRs are estrogen independent, unlike PRs present in other hormoneregulated tumors, such as breast and uterus.…”
Section: Discussionsupporting
confidence: 82%
“…Also, it has been observed that these tumors often grow during pregnancy and luteal phase of the menstrual cycle 2 and there is an association between meningiomas and breast cancer and other tumors wich have hormonal dependency 3,4 . Based in these data, there have been many reports which have dealt with the presence of estrogen receptor (ER) and progesterone receptors (PR) in meningiomas [5][6][7][8][9][10][11][12][13][14][15] . In recent years, the development of monoclonal antibodies specific for steroid hormone receptors has permitted the detection of PR and ER direct in tissue.…”
mentioning
confidence: 99%
“…It has been suggested that the higher estrogen and progesterone levels in the female might influence the growth of meningiomas. 20,21 The intracranial distribution of the meningiomas in our series agrees with that noted in other large series. 5,[14][15][16][17][18][19] Meningiomas of the base were more predominant in females than were those in the vault.…”
Section: Discussionsupporting
confidence: 82%
“…Following the first report in 1979, on the putative presence of oestrogen receptors (ER) in human meningiomas (Donnell et al, 1979), several research groups, including our own (Blankenstein et al, 1983;Martuza et al, 1985) have tried to confirm these findings. Using Scatchard plot analysis (Blaauw et al, 1986) or enzyme immunoassay (Blankenstein et al, 1987) the majority of meningiomas were found to be ER negative.…”
mentioning
confidence: 83%